Mainstream preschool teachers’ skills at identifying and referring children with autism spectrum disorder (ASD) - Mohammed Taresh, Sahar; Ahmad, Nor Aniza; Roslan, Samsilah; Ma'rof, Aini Marina; Mohammed Zaid, Sumaia (Multidisciplinary Digital Publishing Institute, 2020)
Background: Early intervention will help children with autism spectrum disorder (ASD) to attain early learning reinforcement. This study focuses on exploring the ability of preschool teachers to identify children with ASD and their referral decision-making process. Method: This is a mixed-method study (qualitative and quantitative methods) involving 20 respondents. The qualitative study is based on an open question case study, while the quantitative study consists of questionnaire with demographic variables to identify the effect of the demographic variables on the preschool teachers’ ability to identify children with ASD. Sample: The sample was selected via convenience sampling among mainstream preschool teachers. The data was analyzed using SPSS software and thematic analysis. Results: The findings show that preschool teachers did not have skills at identifying children with ASD, and the majority of them labelled children with ASD as spoilt or hyperactive children. They also viewed children with ASD as having other disorders such as attention deficit hyperactivity disorder (ADHD) or communication disorders such as introversion. Moreover, preschool teachers expressed that the reason for the child’s behaviour could be due to the parents’ inability to properly educate their child. Additionally, the demographic variables of the preschool teachers, such as age, education level and teaching experience, were found not to affect their ASD identification skills. Conclusion: Preschool teachers need to improve their skills in identifying ASD among children via training.